An enumeration to the orchids and their conservation status in greater Sylhet, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2016)
The present investigation deals with enumeration including diversity, ecology and conservation of the family Orchidaceae of greater Sylhet region of Bangladesh. Extensive field trips were made at 11 different sites of this region during early monsoon, late monsoon and winter seasons. Relevant literature and different herbaria were consulted to gather information about the orchids of this region. Orchidaceae is represented in greater Sylhet by 75 species under 49 genera. Out of these, 25 species are terrestrial, 48 are epiphytic, one is saprohytic and one is hemiepiphytic. Presence of 37 monotypic genera indicates a narrow diversity in Orchidaceae of this area. The present investigation revealed that 26 orchid species are restricted and distributed only in Sylhet region in Bangladesh. The currently accepted taxonomic nomenclature, synonyms, habit, flowering time, present conservation status and geographical distribution are provided under each taxon.Bangladesh J. Plant Taxon. 23(1): 13-25, 2016 (June)